Silicon-carbon negative electrode material, preparation method thereof and secondary battery
By using a composite of carbon nanotubes and amorphous carbon as a matrix, depositing nanosilicon particles in its pipeline and performing carbon coating, the problems of insufficient compressive resistance and high-temperature storage performance of existing silicon carbon anode materials are solved, and the problem of insufficient compressive resistance and high-temperature storage performance of existing silicon carbon anode materials is achieved. Higher cycle performance and rate performance.
Patent Information
- Application Number
- CN202411681627.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-14
AI Technical Summary
The existing silicon carbon anode materials are prone to structural damage under high compaction density, and the compressive resistance and high-temperature storage performance of porous carbon matrix are insufficient, which affects its cycling performance and rate performance.
Using a composite of carbon nanotubes and amorphous carbon as the matrix, nanosilicon particles are deposited in the pipeline of carbon nanotubes, and the specific surface area is reduced through the carbon cladding layer, improving the dynamic performance of the material and high-temperature storage performance.
It significantly improves the compressive strength, circulation performance and rate performance of silicon carbon anode material, reduces the volume expansion of the material, and improves high-temperature storage performance.
Smart Images

Figure CN119447262A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of material preparation, and in particular to a silicon-carbon negative electrode material and a preparation method thereof, and a secondary battery. Background Art
[0002] Thanks to the advantages of high energy density, long cycle life, and no memory effect, lithium-ion batteries have been increasingly used in electronic products, energy storage technology, and electric vehicles. So far, commercial lithium-ion batteries mainly use graphite as the negative electrode, but the capacity of graphite is close to the maximum theoretical capacity of 372mAh / g. With the demand for higher energy density lithium-ion batteries, silicon with a theoretical capacity of about 4200mAh / g is considered to be one of the most promising negative electrode materials.
[0003] Silicon-based negative electrodes have the advantages of high theoretical capacity, moderate lithium alloying voltage, and abundant raw material sources. However, the huge volume expansion during the lithium alloying process will lead to problems such as silicon particle pulverization, electrical contact loss, and instability of the solid electrolyte interface film, which affects the application of silicon-based negative electrodes. The composite of carbon materials and silicon can effectively alleviate the volume expansion effect of silicon-based negative electrodes and improve electrochemical performance. Therefore, silicon-carbon negative electrode materials are the main research direction of silicon-based negative electrodes.
[0004] At present, silicon-carbon negative electrode materials mainly include grinding silicon-carbon and silane-deposited silicon-carbon. Grinding silicon-carbon prepares nano-silicon through a grinding process, and then composites nano-silicon with carbon through different processes. There are problems such as difficulty in dispersing nano-silicon, high expansion, and complex process. Silane-deposited silicon-carbon is obtained by depositing nano-silicon in the pores of porous carbon through the process of silane cracking. It has the advantages of simple process, low expansion and good cycle performance. However, in deposited silicon-carbon, porous carbon is usually used as the matrix material. Since the skeleton strength of porous carbon is relatively low, the compressive performance of the prepared silicon-carbon negative electrode material is poor. At the same time, porous carbon itself has many defects. The silicon-carbon negative electrode material obtained after vapor deposition of nano-silicon has problems such as low initial efficiency and poor high-temperature storage performance.
[0005] Therefore, how to improve the compressive properties of the matrix material, reduce the defects of the porous structure, and enhance the compressive strength, high-temperature storage and rate performance of the material while maintaining excellent cycle performance is a technical problem that needs to be solved urgently. Summary of the invention
[0006] In view of the problems existing in the above silicon-carbon negative electrode materials, the purpose of the present invention is to provide a silicon-carbon negative electrode material and a preparation method thereof, and a secondary battery. This silicon-carbon negative electrode material has a high compressive strength, which can avoid structural damage of the material under high compaction density, and at the same time construct a conductive network, reduce material defects, improve the dynamic performance and high-temperature storage performance of the material, and enhance the cycle performance and rate performance of the silicon-carbon negative electrode material.
[0007] To achieve the above-mentioned object, the first aspect of the present invention provides a silicon-carbon negative electrode material. The silicon-carbon negative electrode material comprises carbon assembly particles, nano silicon particles and a carbon coating layer. The carbon assembly particles are a composite of carbon nanotubes and amorphous carbon. The nano silicon particles are contained in the tubes of the carbon nanotubes, and the carbon coating layer covers the carbon assembly particles.
[0008] The silicon-carbon negative electrode material of the present invention has at least the following technical effects.
[0009] (1) A composite of carbon nanotubes and amorphous carbon is used to replace traditional porous carbon to deposit nano-silicon particles. Nano-silicon particles are deposited in the pipes of carbon nanotubes. Compared with porous carbon materials, nano-silicon particles have fewer defects, which is beneficial to improving the first coulombic efficiency and high-temperature storage performance of silicon-carbon negative electrode materials.
[0010] (2) Carbon nanotubes are conducive to the construction of a three-dimensional conductive network, which can significantly improve the electron and ion transmission rate of silicon-carbon negative electrode materials, improve the kinetic performance, and thus improve the initial coulombic efficiency and rate performance of silicon-carbon negative electrode materials. In addition, carbon nanotubes have extremely high strength and structural stability. Compared with porous carbon with lower skeleton strength, they can make silicon-carbon negative electrode materials have better compressive resistance, increase the compaction density when the pole piece is subsequently made, and thus improve the energy density of the battery.
[0011] (3) Placing the nano-silicon particles in the carbon nanotube tubes is conducive to the uniform distribution of the nano-silicon particles. At the same time, the carbon nanotubes can inhibit the volume change of the nano-silicon particles in the tubes during the charging and discharging process, effectively reducing the volume expansion of the material and greatly improving the cycle performance of the material.
[0012] (4) The carbon coating layer can reduce the specific surface area of the silicon-carbon negative electrode material, reduce the side reactions caused by the contact between nano-silicon particles and the electrolyte, and at the same time help improve the high-temperature performance of the silicon-carbon negative electrode material.
[0013] In some embodiments, the silicon-carbon negative electrode material satisfies the following relationship,
[0014]
[0015] Wherein, L is the full charge expansion rate of the silicon-carbon negative electrode material, %; M is the percentage of carbon nanotubes in the total mass of the silicon-carbon negative electrode material, %; N is the percentage of the total mass of the silicon-carbon negative electrode material described by the nano-silicon particles, %; ρ is the ultimate compaction density of the silicon-carbon negative electrode material, g / cm 3 ; B is the degree of crushing of carbon assembly particles.
[0016] In some embodiments, 0.75≤B≤1.00.
[0017] In some embodiments, the first reversible capacity of the silicon-carbon negative electrode material is ≥900.0 mAh / g.
[0018] In some embodiments, the first coulombic efficiency of the silicon-carbon negative electrode material is ≥ 89.0%.
[0019] In some embodiments, the 2C discharge capacity retention rate of the silicon-carbon negative electrode material is ≥ 90.0%.
[0020] In some embodiments, the 300-cycle capacity retention rate of the silicon-carbon negative electrode material is ≥88.0%.
[0021] In some embodiments, the first full charge expansion rate of the silicon-carbon negative electrode material is ≤30.0%.
[0022] In some embodiments, the tap density of the silicon-carbon negative electrode material is 0.8 to 1.5 g / cm 3 .
[0023] In some embodiments, the true density of the silicon-carbon negative electrode material is 1.5 to 2.0 g / cm 3 .
[0024] In some embodiments, the ultimate compaction density of the silicon-carbon negative electrode material is 1.5 to 2.0 g / cm 3 .
[0025] In some embodiments, the specific surface area of the silicon-carbon negative electrode material is 1 to 10 m 2 / g.
[0026] In some embodiments, the Dv50 of the silicon-carbon negative electrode material is 3 to 15 μm.
[0027] In some embodiments, the electrical conductivity of the silicon-carbon negative electrode material is 2.0 to 5.0 S / cm.
[0028] In some embodiments, at least a portion of the carbon nanotubes in the carbon assembly particles are nitrogen accessible.
[0029] In some embodiments, the pore volume of the carbon assembly particles is 0.15 to 0.45 cm 3 / g.
[0030] In some embodiments, the average pore size of the carbon assembly particles is 1.5 to 4.5 nm.
[0031] In some embodiments, the porosity of the carbon assembly particles is 20-70%.
[0032] In some embodiments, the specific surface area of the carbon assembly particles is 400 to 1200 m 2 / g.
[0033] In some embodiments, the carbon assembly particles have a Dv50 of 3 to 15 μm.
[0034] In some embodiments, the Dv50 of the carbon assembly particles is less than the average length of the carbon nanotubes.
[0035] In some embodiments, the amorphous carbon includes at least one of soft carbon and hard carbon.
[0036] In some embodiments, the carbon nanotubes include at least one of single-walled carbon nanotubes and multi-walled carbon nanotubes.
[0037] In some embodiments, the average length of the carbon nanotubes is 5 to 20 μm, and the inner diameter of the tubes is 0.5 to 5.0 nm;
[0038] In some embodiments, the carbon nanotubes account for 20-60% of the total mass of the silicon-carbon negative electrode material.
[0039] In some embodiments, the nano silicon particles account for 10-40% of the total mass of the silicon-carbon negative electrode material.
[0040] In some embodiments, the nano silicon particles are amorphous silicon, and the grain size of the amorphous silicon is ≤3 nm.
[0041] In some embodiments, the thickness of the carbon coating layer is 10 to 300 nm.
[0042] In some embodiments, the carbon coating layer is 0.5-10.0% of the total mass of the silicon-carbon negative electrode material.
[0043] The second aspect of the present invention provides a method for preparing a silicon-carbon negative electrode material, comprising the steps of:
[0044] (I) mixing carbon nanotubes, a first carbon source and an organic solvent to obtain a slurry, spray drying the slurry and then carbonizing it to obtain a carbon precursor, wherein the inner diameter of the carbon nanotubes is d, the average length of the carbon nanotubes is L, and 0.5 nm≤d≤5.0 nm;
[0045] (II) the carbon precursor is crushed to obtain carbon assembly particles, the carbon assembly particles have a crushing degree of B, 0.75≤B≤1.00, and L is greater than or equal to Dv50 of the carbon assembly particles;
[0046] (III) The carbon assembly particles are subjected to vapor phase silicon deposition and then carbon-coated with a second carbon source.
[0047] In the preparation method of the silicon-carbon negative electrode material of the present invention, carbon nanotubes, a first carbon source and an organic solvent are stirred and mixed to obtain a carbon precursor slurry, which is then spray-dried and carbonized in sequence to obtain a carbon precursor; the carbon precursor is then pulverized to obtain carbon assembly particles containing open-pore carbon nanotubes, and gas-phase silicon enters its pipes through the openings of the carbon nanotubes for deposition. In addition, by selecting carbon nanotubes with a certain pipe inner diameter and average length and controlling the particle size of the carbon assembly particles, it is possible to ensure that the carbon nanotubes have a certain pore volume so that a sufficient amount of nano-silicon particles can be uniformly deposited. The carbon assembly particles need to have a certain degree of pulverization so that after the carbon precursor is pulverized, the carbon nanotubes have sufficient openings to allow gas-phase silicon to enter the pipes.
[0048] In some embodiments, the first carbon source includes at least one of petroleum coke, asphalt, phenolic resin, urea-formaldehyde resin, polyamide resin, epoxy resin, polyimide, polyvinyl pyrrolidone, polyvinyl alcohol, polyacrylonitrile, polydopamine, sucrose, glucose, starch, lignin, and citric acid.
[0049] In some embodiments, the organic solvent includes at least one of methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, propylene glycol, benzene, toluene, xylene, hexane, n-hexane, and cyclohexane.
[0050] In some embodiments, the mass ratio of the carbon nanotubes, the first carbon source, and the organic solvent is 1:0.5-5:1-20.
[0051] In some embodiments, stirring is performed during mixing, the stirring speed is 100 to 1000 rpm, and the stirring time is 1 to 10 hours.
[0052] In some embodiments, the feed inlet temperature of the spray drying is 120-250°C, and the discharge outlet temperature of the spray drying is 70-110°C.
[0053] In some embodiments, the carbonization temperature is 600-1000° C., and the carbonization time is 1-10 h.
[0054] In some embodiments, the carbonization is performed in a protective gas, and the protective gas is at least one of nitrogen, helium, neon, argon, krypton, and xenon.
[0055] In some embodiments, the carbon assembly particles have a Dv50 of 5 to 25 μm.
[0056] In some embodiments, the pulverization is performed using a jet mill.
[0057] In some embodiments, the carbon coating temperature is 500-900° C., and the carbon coating time is 1-8 hours.
[0058] In some embodiments, the second carbon source is a gaseous carbon source, and the gaseous carbon source includes at least one of methane, ethane, propane, butane, isobutane, ethylene, propylene, butene and acetylene.
[0059] In some embodiments, the second carbon source is a gaseous carbon source, and the volume concentration of the gaseous carbon source is 5 to 50%.
[0060] In some embodiments, the carbon coating is performed in a protective gas, and the protective gas is at least one of nitrogen, helium, neon, argon, krypton, and xenon.
[0061] In some embodiments, the carbon coating process further includes sequentially performing disintegration, screening, and demagnetization treatments.
[0062] In some embodiments, vapor phase silicon deposition comprises the step of subjecting carbon assembly particles and silicon source gas to chemical vapor deposition in a high temperature environment.
[0063] In some embodiments, the high temperature environment has a temperature of 400-700°C.
[0064] In some embodiments, the chemical vapor deposition time is 1 to 8 hours.
[0065] In some embodiments, the silicon source gas includes at least one of monosilane, disilane, trisilane, monochlorotrihydrogensilane, dichlorodihydrogensilane, and trichlorosilane.
[0066] In some embodiments, the volume concentration of the silicon source gas is 5 to 40%.
[0067] In some embodiments, the nano-silicon particles formed during the pyrolysis of the silicon source gas are at least partially distributed in the channels of the carbon nanotubes in the carbon assembly.
[0068] In some embodiments, vapor phase silicon deposition is performed in a protective gas, the protective gas being at least one of nitrogen, helium, neon, argon, krypton, and xenon.
[0069] The present invention also provides an application of the silicon-carbon negative electrode material in the negative electrode and a secondary battery, comprising a positive electrode active material, a negative electrode active material and an electrolyte. The negative electrode active material is the aforementioned silicon-carbon negative electrode material or the silicon-carbon negative electrode material prepared by the aforementioned method for preparing the silicon-carbon negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0070] Figure 1 It is a schematic structural diagram of the silicon-carbon negative electrode material of the present invention.
[0071] Figure 2 It is the particle size distribution curve of the carbon precursor and the carbon assembly in the silicon-carbon negative electrode material of the present invention. DETAILED DESCRIPTION
[0072] The silicon-carbon negative electrode material of the present invention can be used alone or mixed with other negative electrode active materials (such as natural graphite, artificial graphite, soft carbon and / or hard carbon, etc.). The silicon-carbon negative electrode material can be applied to secondary batteries, which include positive electrode active materials and negative electrode active materials. The positive electrode active material includes at least one of a lithium cobalt oxide positive electrode material, a lithium iron phosphate positive electrode material, a nickel cobalt manganese oxide positive electrode material, and a nickel cobalt aluminum oxide positive electrode material.
[0073] The first reversible capacity of the silicon-carbon negative electrode material of the present invention is ≥900.0mAh / g, and as an example, it can be, but not limited to, ≥900.0mAh / g, ≥1000.0mAh / g, ≥1100.0mAh / g, ≥1200.0mAh / g, ≥13000mAh / g, ≥1400.0mAh / g, ≥15000mAh / g, ≥1600.0mAh / g, ≥1700.0mAh / g, ≥1800.0mAh / g. The first coulombic efficiency of the silicon-carbon negative electrode material is ≥89.0%, and as an example, it can be, but not limited to, ≥89.0%, ≥90.0%, ≥91.0%, ≥92.0%, ≥92.3%, ≥94.0%, ≥95.0%. The 2C discharge capacity retention rate of the silicon-carbon negative electrode material is ≥90.0%. As an example, it can be but not limited to ≥90.0%, ≥90.5%, ≥91.0%, ≥91.5%, ≥92.0%, ≥92.5%, ≥93.0%, ≥93.5%, ≥94.0%, ≥94.4%, ≥94.8%, ≥95.0%, ≥95.6%, ≥95.8%, ≥96.0%, and ≥96.5%. The 300-week capacity retention rate of the silicon-carbon negative electrode material is ≥88.0%. As an example, it can be, but not limited to, ≥88.0%, ≥88.3%, ≥88.6%, ≥89.0%, ≥89.4%, ≥89.8%, ≥90.0%, ≥90.4%, ≥90.8%, ≥91.0%, ≥91.4%, ≥91.8%, ≥92.0%, ≥92.4%, ≥92.8%, ≥93.0%, ≥93.5%, ≥94.0%. The first full charge expansion rate of the silicon-carbon negative electrode material is ≤30.0%. As an example, it can be, but not limited to, ≤30.0%, ≤29.0%, ≤28.0%, ≤27.0%, 26.0%, ≤25.0%, ≤24.0%.
[0074] The tap density of the silicon-carbon negative electrode material of the present invention is 0.8 to 1.5 g / cm 3 As an example, it can be, but is not limited to, 0.8 g / cm 3 , 0.9g / cm 3 , 1.0g / cm 3 , 1.1g / cm 3, 1.2g / cm 3 , 1.3g / cm 3 , 1.4g / cm 3 , 1.5g / cm 3 The true density of silicon-carbon negative electrode material is 1.5-2.0 g / cm 3 As an example, it can be, but is not limited to, 1.5 g / cm 3 , 1.6g / cm 3 , 1.7g / cm 3 , 1.8g / cm 3 , 1.9g / cm 3 , 2.0g / cm 3 The ultimate compaction density of silicon-carbon negative electrode materials is 1.5-2.0 g / cm 3 As an example, it can be, but is not limited to, 1.5 g / cm 3 , 1.6g / cm 3 , 1.7g / cm 3 , 1.8g / cm 3 , 1.9g / cm 3 , 2.0g / cm 3 The specific surface area of silicon-carbon negative electrode material is 1 to 10 m 2 / g, as an example, it can be but not limited to 1m 2 / g, 2m 2 / g, 3m 2 / g, 4m 2 / g, 5m 2 / g, 6m 2 / g, 7m 2 / g, 8m 2 / g, 9m 2 / g, 10m 2 / g. The Dv50 of the silicon-carbon negative electrode material is 3 to 15 μm. As an example, it can be, but not limited to, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, and 15 μm. The conductivity of the silicon-carbon negative electrode material is 2.0 to 5.0 S / cm. As an example, it can be, but not limited to, 2.0 S / cm, 2.5 S / cm, 3.0 S / cm, 3.5 S / cm, 4.0 S / cm, 4.5 S / cm, and 5.0 S / cm.
[0075] The structure of the silicon-carbon negative electrode material of the present invention can be Figure 1 An example is given below. Figure 1As shown, the silicon-carbon anode material 100 includes carbon assembly particles 10, nano-silicon particles 30, and a carbon coating layer 50. The carbon assembly particles 10 are a composite of carbon nanotubes 11 and amorphous carbon 13. The nano-silicon particles 30 are accommodated within the channels of the carbon nanotubes 11, and the carbon coating layer 50 coats the carbon assembly particles 10.
[0076] The silicon-carbon anode material satisfies the following relationship.
[0077]
[0078] Wherein, L is the full charge expansion rate of the silicon-carbon anode material, %; M is the percentage of carbon nanotubes in the total mass of the silicon-carbon anode material, %; N is the percentage of nano-silicon particles in the total mass of the silicon-carbon anode material, %; ρ is the ultimate compaction density of the silicon-carbon anode material, g / cm 3 ; B is the degree of pulverization of the carbon assembly particles.
[0079] The calculation method of B is as follows: The area of the particle size distribution curve of the carbon precursor before pulverization is A1, the area of the particle size distribution curve of the obtained carbon assembly particles after pulverization is A2, and the overlapping area of the two particle size distribution curves is A3 (as Figure 2 shown), B = 1 - A3 / (A1 + A2). When the B value ≥ 0.75, it indicates that the pulverization degree of the carbon precursor is relatively high, and more large particle carbon precursors are pulverized into carbon assemblies with the target particle size. The carbon nanotubes in the carbon assemblies are likely to form an open structure, that is, the channels of the carbon nanotubes are accessible to nitrogen, which can ensure that the carbon assemblies have a certain pore volume, enabling the nano-silicon particles formed by the pyrolysis of the silicon source gas to be deposited in the channels of the carbon nanotubes of the carbon assemblies. When the B value < 0.75, it indicates that the pulverization degree of the carbon precursor is not high, and more carbon precursors have not been pulverized. More carbon nanotubes in the carbon assemblies are wrapped by amorphous carbon inside the particles and do not form an open structure, resulting in more nano-silicon being deposited on the surface of the carbon assemblies.
[0080] N < M, 0.75 ≤ B ≤ 1.00. Under this parameter, it indicates that the relative contents of carbon nanotubes and nano-silicon particles are moderate, and there is a certain degree of pulverization, so that after the carbon precursor is pulverized, the carbon nanotubes have sufficient openings for gaseous silicon to enter the channels. Therefore, the nano-silicon particles are evenly distributed in the channels of the carbon nanotubes. The carbon nanotubes can inhibit the volume change of the nano-silicon particles in the channels, which is beneficial to reducing the expansion rate of the silicon-carbon anode material. In addition, the extremely high strength and structural stability of the carbon nanotubes are beneficial to improving the compressive performance of the silicon-carbon anode material, and the constructed three-dimensional conductive network is beneficial to improving the kinetic performance and rate performance.
[0081] Furthermore, at least some of the carbon nanotubes in the carbon assembly particles are accessible to nitrogen, which is beneficial to the deposition of gaseous silicon in an inert atmosphere. The pore volume of the carbon assembly particles is 0.15 - 0.45 cm3 / g, as an example, the pore volume can be but is not limited to 0.15cm 3 / g, 0.20cm 3 / g, 0.25cm 3 / g, 0.30cm 3 / g, 0.35cm 3 / g, 0.40cm 3 / g, 0.45cm 3 The average pore size of the carbon assembly particles is 1.5-4.5 nm. For example, the average pore size may be, but is not limited to, 1.5 nm, 2.0 nm, 2.5 nm, 3.0 nm, 3.5 nm, 4.0 nm, and 4.5 nm.
[0082] The porosity of the carbon assembly particles is 20-70%, and as examples, it can be, but is not limited to, 20%, 30%, 40%, 50%, 60%, and 70%. The specific surface area of the carbon assembly particles is 400-1200 m 2 / g, as an example, it can be but not limited to 400m 2 / g、500m 2 / g, 600m 2 / g、700m 2 / g、800m 2 / g、900m 2 / g、1000m 2 / g、1100m 2 / g、1200m 2 / g. The Dv50 of the carbon assembly particles is 3 to 15 μm, and as an example, it can be but not limited to 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, and 15 μm. The Dv50 of the carbon assembly particles is smaller than the average length of the carbon nanotubes. By controlling the particle size of the carbon assembly particles, it is possible to ensure that the carbon nanotubes have more openings so as to deposit a sufficient amount of nano-silicon particles.
[0083] The carbon nanotubes include at least one of single-walled carbon nanotubes and multi-walled carbon nanotubes. The average length of the carbon nanotubes is 5 to 20 μm. As an example, the average length can be but not limited to 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm. The inner diameter of the carbon nanotube is 0.5 to 5.0 nm. As an example, the inner diameter of the carbon nanotube can be but not limited to 0.5 nm, 1.0 nm, 1.5 nm, 2.0 nm, 2.5 nm, 3.0 nm, 3.5 nm, 4.0 nm, 4.5 nm, 5.0 nm. By selecting carbon nanotubes with a certain inner diameter and average length, it is possible to ensure that the carbon nanotubes have a certain pore volume so as to uniformly deposit a sufficient amount of nano-silicon particles. The carbon nanotubes account for 20-60% of the total mass of the silicon-carbon negative electrode material. As an example, it can be but not limited to 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%.
[0084] The nano silicon particles are 10-40% of the total mass of the silicon-carbon negative electrode material. As an example, it can be but not limited to 10%, 15%, 20%, 25%, 30%, 35%, 40%. The nano silicon particles are amorphous silicon, and the grain size of amorphous silicon is ≤3nm. Amorphous carbon includes at least one of soft carbon and hard carbon. The thickness of the carbon coating layer is 10-300nm. As an example, the thickness can be but not limited to 10nm, 30nm, 50nm, 70nm, 100nm, 130nm, 150nm, 180nm, 200nm, 230nm, 250nm, 270nm, 300nm. The carbon coating layer is 0.5 to 10.0% of the total mass of the silicon-carbon negative electrode material. As an example, it can be but not limited to 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5%, 8.0%, 9.0%, and 10.0%.
[0085] The method for preparing the silicon-carbon negative electrode material of the present invention may include the steps of:
[0086] (I) carbon nanotubes, a first carbon source and an organic solvent are mixed to obtain a slurry, and the slurry is spray-dried and then carbonized to obtain a carbon precursor.
[0087] (II) The carbon precursor is crushed to obtain carbon assembly particles.
[0088] (III) The carbon assembly particles are subjected to vapor phase silicon deposition and then carbon-coated with a second carbon source.
[0089] Wherein, in step (I), the inner diameter of the carbon nanotube is d, the average length of the carbon nanotube is L, 0.5nm≤d≤5.0nm, and L is greater than or equal to the Dv50 of the carbon assembly particles. The first carbon source includes at least one of petroleum coke, asphalt, phenolic resin, urea-formaldehyde resin, polyamide resin, epoxy resin, polyimide, polyvinyl pyrrolidone, polyvinyl alcohol, polyacrylonitrile, polydopamine, sucrose, glucose, starch, lignin, and citric acid. The organic solvent includes at least one of methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, propylene glycol, benzene, toluene, xylene, hexane, n-hexane, and cyclohexane. The mass ratio of the carbon nanotubes, the first carbon source and the organic solvent is 1:0.5-5:1-20. As an example, the mass ratio of the three can be but is not limited to 1:0.5:1, 1:0.5:5, 1:0.5:10, 1:0.5:15, 1:0.5:20, 1:1.5:1, 1:1.5:5, 1:1.5:10, 1:1.5:15, 1:1.5:20, 1:3.0:1, 1:3.0:5, 1:3.0:10, 1:3.0:15, 1:3.0:20, 1:5.0:1, 1:5.0:5, 1:5.0:10, 1:5.0:15, 1:5.0:20.
[0090] Stirring is performed during mixing, and the stirring speed is 100-1000rpm. As an example, the speed can be, but not limited to, 100rpm, 200rpm, 300rpm, 400rpm, 500rpm, 600rpm, 700rpm, 800rpm, 900rpm, and 1000rpm. The stirring time is 1-10h. As an example, the time can be, but not limited to, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, and 10h. The feed inlet temperature of spray drying is 120-250°C. As an example, it can be, but not limited to, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, and 250°C. The discharge port temperature of the spray drying is 70-110°C. As an example, it can be, but not limited to, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, and 110°C. The temperature of the carbonization is 600-1000°C. As an example, it can be, but not limited to, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, and 1000°C. The carbonization time is 1-10h. As an example, it can be, but not limited to, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, and 10h. The carbonization is carried out in a protective gas, and the protective gas is at least one of nitrogen, helium, neon, argon, krypton, and xenon;
[0091] In step (II), the pulverization is performed by a jet mill. The degree of pulverization of the carbon assembly particles is B, 0.75≤B≤1.0. The average length L of the carbon nanotubes is greater than or equal to the Dv50 of the carbon assembly particles, and the Dv50 of the carbon assembly particles is 5 to 25 μm. The carbon precursor is pulverized into small-sized carbon assembly particles, and the degree of pulverization is until the carbon assembly particles are small, exposing the openings of the carbon nanotubes to prepare for the gas phase silicon to enter the pipeline.
[0092] In step (III), vapor phase silicon deposition includes the steps of: chemical vapor deposition of carbon assembly particles and silicon source gas in a high temperature environment. Further, the temperature of the high temperature environment is 400-700°C. As an example, the temperature can be, but not limited to, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, and 700°C. The time of chemical vapor deposition is 1-8h. As an example, the time can be, but not limited to, 1h, 2h, 3h, 4h, 5h, 6h, 7h, and 8h. The silicon source gas includes at least one of monosilane, disilane, trisilane, monochlorotrihydrogen silicon, dichlorodihydrogen silicon, and trichlorosilane. The volume concentration of the silicon source gas is 5-40%. As an example, the volume concentration can be, but not limited to, 5%, 10%, 15%, 20%, 25%, 30%, 35%, and 40%. The nano silicon particles formed by the pyrolysis of the silicon source gas are at least partially distributed in the channels of the carbon nanotubes in the carbon assembly. The vapor phase silicon deposition is carried out in a protective gas, which is at least one of nitrogen, helium, neon, argon, krypton and xenon.
[0093] The temperature of carbon coating is 500-900°C. As an example, it can be, but not limited to, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, and 900°C. The time of carbon coating is 1-8h. As an example, the time of carbon coating can be, but not limited to, 1h, 2h, 3h, 4h, 5h, 6h, 7h, and 8h. The second carbon source is a gaseous carbon source, and the gaseous carbon source includes at least one of methane, ethane, propane, butane, isobutane, ethylene, propylene, butene, and acetylene. The volume concentration of the gaseous carbon source is 5-50%. As an example, it can be, but not limited to, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, and 50%. The carbon coating is carried out in a protective gas, wherein the protective gas is at least one of nitrogen, helium, neon, argon, krypton and xenon. After the carbon coating, the process also includes sequentially breaking up, screening and demagnetizing treatment.
[0094] In order to better illustrate the purpose, technical scheme and beneficial effects of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be noted that the following implementation method is a further explanation of the present invention and should not be used as a limitation of the present invention. The embodiments of the present invention include a description of the technical scheme of the silicon-carbon negative electrode material and a description of the technical scheme of the preparation method of the silicon-carbon negative electrode material.
[0095] Example 1
[0096] This embodiment is a method for preparing a silicon-carbon negative electrode material, which includes the following steps.
[0097] (I) Carbon nanotubes (single-walled carbon nanotubes, with an average length of 12 μm and an inner diameter of 2.5 nm, 500 g), asphalt and n-hexane were stirred and mixed at a mass ratio of 1:1:4 at 800 rpm for 1 h to obtain a slurry, which was then spray-dried (inlet air temperature 160°C, outlet air temperature 80°C), and then carbonized at 800°C in a nitrogen atmosphere for 4 h to obtain a carbon precursor with a Dv50 of 14.7 μm.
[0098] (II) The carbon precursor is pulverized by a jet mill to obtain carbon assembly particles with a Dv50 of 6.8 μm. The pulverization degree B of the carbon assembly particles is 0.84.
[0099] (III) 600 g of carbon assembly particles were placed in a deposition furnace, air was removed until the oxygen content was less than 50 ppm, and the mixture was heated to 500° C. in a nitrogen atmosphere, and monosilane with a volume concentration of 12.5% was introduced to perform silicon deposition for 2 h. The mixture was then heated to 680° C., and acetylene with a volume concentration of 10% was introduced to perform carbon coating for 2 h in a nitrogen atmosphere, and then the mixture was broken up, sieved, and demagnetized to obtain a silicon-carbon negative electrode material with a carbon coating layer thickness of 50 nm.
[0100] Example 2
[0101] This embodiment is a method for preparing a silicon-carbon negative electrode material, which includes the following steps.
[0102] (I) Carbon nanotubes (single-walled carbon nanotubes, with an average length of 12 μm and an inner diameter of 2.5 nm, 500 g), asphalt and n-hexane were stirred and mixed at a mass ratio of 1:1.6:5 at 800 rpm for 1 h to obtain a slurry, which was then spray-dried (inlet air temperature 160°C, outlet air temperature 80°C), and then carbonized at 800°C in a nitrogen atmosphere for 4 h to obtain a carbon precursor with a Dv50 of 15.1 μm.
[0103] (II) The carbon precursor is pulverized by a jet mill to obtain carbon assembly particles with a Dv50 of 7.5 μm and a pulverization degree B of 0.83.
[0104] (III) 600 g of carbon assembly particles were placed in a deposition furnace, air was removed until the oxygen content was less than 50 ppm, and the mixture was heated to 500° C. in a nitrogen atmosphere, and monosilane with a volume concentration of 12.5% was introduced to perform silicon deposition for 1.5 h. The mixture was then heated to 680° C., and acetylene with a volume concentration of 15% was introduced to perform carbon coating for 1 h in a nitrogen atmosphere, and then the mixture was broken up, sieved, and demagnetized to obtain a silicon-carbon negative electrode material with a carbon coating layer thickness of 35 nm.
[0105] Example 3
[0106] This embodiment is a method for preparing a silicon-carbon negative electrode material, which includes the following steps.
[0107] (I) Carbon nanotubes (single-walled carbon nanotubes, with an average length of 10 μm and an inner diameter of 2.0 nm, 500 g), asphalt and n-hexane were stirred and mixed at a mass ratio of 1:1:5 at 800 rpm for 1 h to obtain a slurry, and the slurry was spray dried (inlet air temperature 160°C, outlet air temperature 80°C), and then carbonized in a nitrogen atmosphere at 800°C for 4 h to obtain a carbon precursor with a Dv50 of 12.9 μm.
[0108] (II) The carbon precursor is pulverized by a jet mill to obtain carbon assembly particles with a Dv50 of 8.7 μm and a pulverization degree B of 0.81.
[0109] (III) 600 g of carbon assembly particles were placed in a deposition furnace, air was removed until the oxygen content was less than 50 ppm, and the particles were heated to 500° C. in a nitrogen atmosphere, and monosilane with a volume concentration of 15.0% was introduced to perform silicon deposition for 1.5 h. The particles were then heated to 750° C., and acetylene with a volume concentration of 10% was introduced to perform carbon coating for 1.5 h in a nitrogen atmosphere, and then the particles were broken up, sieved, and demagnetized to obtain a silicon-carbon negative electrode material with a carbon coating layer thickness of 40 nm.
[0110] Example 4
[0111] This embodiment is a method for preparing a silicon-carbon negative electrode material, which includes the following steps.
[0112] (I) Carbon nanotubes (single-walled carbon nanotubes, with an average length of 10 μm and an inner diameter of 2.0 nm, 500 g), asphalt and n-hexane were stirred and mixed at a mass ratio of 1:1.2:5 at 800 rpm for 1 h to obtain a slurry, which was then spray-dried (inlet air temperature 160°C, outlet air temperature 80°C), and then carbonized at 800°C in a nitrogen atmosphere for 4 h to obtain a carbon precursor with a Dv50 of 13.6 μm.
[0113] (II) The carbon precursor is pulverized by a jet mill to obtain carbon assembly particles with a Dv50 of 6.4 μm and a pulverization degree B of 0.92.
[0114] (III) 800 g of carbon assembly particles were placed in a deposition furnace, air was removed until the oxygen content was less than 50 ppm, and the particles were heated to 500° C. in a nitrogen atmosphere, and monosilane with a volume concentration of 15.0% was introduced to perform silicon deposition for 2 hours. The particles were then heated to 800° C., and ethylene with a volume concentration of 12% was introduced to perform carbon coating for 1.5 hours in a nitrogen atmosphere. The particles were then broken up, sieved, and demagnetized to obtain a silicon-carbon negative electrode material with a carbon coating layer thickness of 45 nm.
[0115] Example 5
[0116] This embodiment is a method for preparing a silicon-carbon negative electrode material, which includes the following steps.
[0117] (I) Carbon nanotubes (single-walled carbon nanotubes, with an average length of 12 μm and an inner diameter of 2.5 nm, 500 g), phenolic resin and ethanol were stirred and mixed at a mass ratio of 1:1.2:5 at 800 rpm for 1 h to obtain a slurry, and the slurry was spray dried (inlet air temperature 180°C, outlet air temperature 90°C), and then carbonized at 900°C in a nitrogen atmosphere for 5 h to obtain a carbon precursor with a Dv50 of 13.1 μm.
[0118] (II) The carbon precursor is pulverized by a jet mill to obtain carbon assembly particles with a Dv50 of 8.2 μm. The pulverization degree B of the carbon assembly particles is 0.79.
[0119] (III) 800 g of carbon assembly particles were placed in a deposition furnace, air was removed until the oxygen content was less than 50 ppm, and the particles were heated to 500° C. in a nitrogen atmosphere, and monosilane with a volume concentration of 12.5% was introduced to perform silicon deposition for 2 hours. The particles were then heated to 750° C., and acetylene with a volume concentration of 20% was introduced to perform carbon coating for 1 hour in a nitrogen atmosphere, and then the particles were broken up, sieved, and demagnetized to obtain a silicon-carbon negative electrode material with a carbon coating layer thickness of 45 nm.
[0120] Example 6
[0121] This embodiment is a method for preparing a silicon-carbon negative electrode material, which includes the following steps.
[0122] (I) Carbon nanotubes (single-walled carbon nanotubes, with an average length of 12 μm and an inner diameter of 2.5 nm, 500 g), phenolic resin and ethanol were stirred and mixed at a mass ratio of 1:1.6:6.4 at a speed of 1000 rpm for 1 h to obtain a slurry, and the slurry was spray dried (inlet air temperature 180°C, outlet air temperature 90°C), and then carbonized at 900°C in a nitrogen atmosphere for 5 h to obtain a carbon precursor with a Dv50 of 12.5 μm.
[0123] (II) The carbon precursor is pulverized by a jet mill to obtain carbon assembly particles with a Dv50 of 7.0 μm. The pulverization degree B of the carbon assembly particles is 0.88.
[0124] (III) 1000 g of carbon assembly particles were placed in a deposition furnace, air was removed until the oxygen content was less than 50 ppm, and the particles were heated to 550° C. in a nitrogen atmosphere, and monosilane with a volume concentration of 6.0% was introduced to perform silicon deposition for 4 hours. The particles were then heated to 750° C., and acetylene with a volume concentration of 10% was introduced to perform carbon coating for 1.5 hours in a nitrogen atmosphere. The particles were then broken up, sieved, and demagnetized to obtain a silicon-carbon negative electrode material with a carbon coating layer thickness of 25 nm.
[0125] Example 7
[0126] This embodiment is a method for preparing a silicon-carbon negative electrode material, which includes the following steps.
[0127] (I) Carbon nanotubes (multi-walled carbon nanotubes, with an average length of 10 μm and an inner diameter of 2.0 nm, 500 g), phenolic formaldehyde and ethanol were stirred and mixed at a mass ratio of 1:2.4:8.5 at 800 rpm for 1.5 h to obtain a slurry, and the slurry was spray dried (inlet air temperature 180°C, outlet air temperature 90°C), and then carbonized at 900°C in a nitrogen atmosphere for 5 h to obtain a carbon precursor with a Dv50 of 12.4 μm.
[0128] (II) The carbon precursor is pulverized by a jet mill to obtain carbon assembly particles with a Dv50 of 7.5 μm and a pulverization degree B of 0.80.
[0129] (III) 1000 g of carbon assembly particles were placed in a deposition furnace, air was removed until the oxygen content was less than 50 ppm, and the particles were heated to 500° C. in a nitrogen atmosphere, and 10.0% disilane was introduced to deposit silicon for 1 hour. The particles were then heated to 800° C., and 10% propane was introduced to deposit carbon for 1 hour in a nitrogen atmosphere. The particles were then broken up, sieved, and demagnetized to obtain a silicon-carbon negative electrode material with a carbon coating layer thickness of 30 nm.
[0130] Comparative Example 1
[0131] This comparative example is a method for preparing a silicon-carbon negative electrode material, which includes the following steps.
[0132] Take 600g of porous carbon with a Dv50 of 6.8μm and place it in a deposition furnace. Expel the air until the oxygen content is less than 50ppm. Heat it to 500℃ in a nitrogen atmosphere, introduce 12.5% monosilane by volume, and carry out silicon deposition for 2h; continue to heat it to 680℃, introduce 10% acetylene by volume, and carry out carbon coating for 2h. Then, after breaking up, screening, and demagnetization, a silicon-carbon negative electrode material with a carbon coating layer thickness of 45nm is obtained.
[0133] Comparative Example 2
[0134] This comparative example is a method for preparing a silicon-carbon negative electrode material, which includes the following steps.
[0135] (I) Carbon nanotubes (single-walled carbon nanotubes, with an average length of 6 μm and an inner diameter of 2.5 nm, 500 g), asphalt and n-hexane were stirred and mixed at a mass ratio of 1:1:4 at 800 rpm for 1 h to obtain a slurry, which was then spray-dried (inlet air temperature 160°C, outlet air temperature 80°C), and then carbonized at 800°C in a nitrogen atmosphere for 4 h to obtain a carbon precursor with a Dv50 of 14.2 μm.
[0136] (II) The carbon precursor is pulverized by a jet mill to obtain carbon assembly particles with a Dv50 of 7.0 μm and a pulverization degree B of 0.81.
[0137] (III) 600 g of carbon assembly particles were placed in a deposition furnace, air was removed until the oxygen content was less than 50 ppm, and the mixture was heated to 500° C. in a nitrogen atmosphere, and monosilane with a volume concentration of 12.5% was introduced to perform silicon deposition for 2 h. The mixture was then heated to 680° C., and acetylene with a volume concentration of 10% was introduced to perform carbon coating for 2 h in a nitrogen atmosphere, and then the mixture was broken up, sieved, and demagnetized to obtain a silicon-carbon negative electrode material with a carbon coating layer thickness of 50 nm.
[0138] Comparative Example 3
[0139] This comparative example is a method for preparing a silicon-carbon negative electrode material, which includes the following steps.
[0140] (I) Carbon nanotubes (single-walled carbon nanotubes, with an average length of 12 μm and an inner diameter of 2.5 nm, 500 g), asphalt and n-hexane were stirred and mixed at a mass ratio of 1:1:4 at 800 rpm for 1 h to obtain a slurry, which was then spray-dried (inlet air temperature 160°C, outlet air temperature 80°C), and then carbonized at 800°C in a nitrogen atmosphere for 4 h to obtain a carbon precursor with a Dv50 of 14.7 μm.
[0141] (II) The carbon precursor is pulverized by a jet mill to obtain carbon assembly particles with a Dv50 of 9.7 μm and a pulverization degree B of 0.70.
[0142] (III) 600 g of carbon assembly particles were placed in a deposition furnace, air was removed until the oxygen content was less than 50 ppm, and the mixture was heated to 500° C. in a nitrogen atmosphere, and monosilane with a volume concentration of 12.5% was introduced to perform silicon deposition for 2 h. The mixture was then heated to 680° C., and acetylene with a volume concentration of 10% was introduced to perform carbon coating for 2 h in a nitrogen atmosphere, and then the mixture was broken up, sieved, and demagnetized to obtain a silicon-carbon negative electrode material with a carbon coating layer thickness of 50 nm.
[0143] Comparative Example 4
[0144] This comparative example is a method for preparing a silicon-carbon negative electrode material, which includes the following steps.
[0145] (I) Carbon nanotubes (single-walled carbon nanotubes, with an average length of 12 μm and an inner diameter of 8.0 nm, 500 g), asphalt and n-hexane were stirred and mixed at a mass ratio of 1:1:4 at 800 rpm for 1 h to obtain a slurry, which was then spray-dried (inlet air temperature 160°C, outlet air temperature 80°C), and then carbonized at 800°C in a nitrogen atmosphere for 4 h to obtain a carbon precursor with a Dv50 of 12.8 μm.
[0146] (II) The carbon precursor is pulverized by a jet mill to obtain carbon assembly particles with a Dv50 of 8.0 μm. The pulverization degree B of the carbon assembly particles is 0.83.
[0147] (III) 600 g of carbon assembly particles were placed in a deposition furnace, air was removed until the oxygen content was less than 50 ppm, and the mixture was heated to 500° C. in a nitrogen atmosphere, and monosilane with a volume concentration of 12.5% was introduced to perform silicon deposition for 2 h. The mixture was then heated to 680° C., and acetylene with a volume concentration of 10% was introduced to perform carbon coating for 2 h in a nitrogen atmosphere, and then the mixture was broken up, sieved, and demagnetized to obtain a silicon-carbon negative electrode material with a carbon coating layer thickness of 50 nm.
[0148] The carbon assembly particles obtained in step (II) of the preparation method of silicon-carbon negative electrode materials in Examples 1 to 7 and Comparative Examples 1 to 4 were tested for physical properties, and the results are shown in Table 1. The specific surface area, average pore size, pore volume and pore size distribution curve were obtained by nitrogen isothermal adsorption-desorption curve test. The porosity was obtained by mercury intrusion testing.
[0149] Table 1 Physical properties of carbon assembly particles of Examples 1 to 7 and Comparative Examples 1 to 4
[0150]
[0151]
[0152] From the results in Table 1, it can be seen that by pulverizing the carbon precursor to a B value of 0.75 to 1.00, carbon assembly particles with a high pore volume and porosity can be obtained.
[0153] The physical properties, chemical composition and electrochemical performance of the silicon-carbon negative electrode materials prepared in Examples 1 to 7 and Comparative Examples 1 to 4 were tested under the following test conditions. The test results are shown in Table 2.
[0154] (1) Physical properties
[0155] The particle size distribution was obtained by laser particle size analyzer.
[0156] The tap density is obtained by using a tap density meter.
[0157] The true density is obtained by testing with a true density meter.
[0158] The conductivity was obtained using a powder conductivity tester.
[0159] The powder compaction density meter was used to test the rebound rate and the powder compaction density ρ at the maximum rebound rate, that is, the ultimate compaction density.
[0160] (2) Chemical composition test
[0161] The carbon content was obtained by using a carbon-sulfur analyzer.
[0162] The silicon content was measured by inductively coupled plasma atomic emission spectrometry.
[0163] (3) Gram capacity performance test
[0164] The silicon-carbon negative electrode materials prepared in Examples 1 to 7 and Comparative Examples 1 to 4 were respectively used as active materials, mixed with a water dispersion of a binder acrylonitrile multipolymer (LA132, solid content 15%) and a conductive agent (Super-P) in a mass ratio of 92:6:2, added with a certain amount of water as a solvent, homogenized, and the solid content of the slurry was adjusted to 55%, coated on copper foil, and vacuum dried and rolled to prepare a negative electrode sheet. The counter electrode was a metal lithium sheet, and the electrolyte was 1 mol / L LiPF 6 The solution (the solvent is a mixture of EC, DMC and EMC in a volume ratio of 1:1:1) and the separator is a polypropylene microporous membrane, which is assembled into a CR2032 button cell in a glove box filled with inert gas. The charge and discharge test of the button cell is carried out on the LANHE battery test system of LANHE Electronics Co., Ltd.
[0165] The first charge and discharge performance test: At room temperature, discharge at a constant current of 0.1C to a voltage of 0.01V, then discharge at a constant current of 0.02C to a voltage of 0.005V, and charge at a constant current of 0.1C to a voltage of 1.5V to obtain the first reversible capacity and the first coulombic efficiency.
[0166] (4) Electrochemical performance test
[0167] The silicon-carbon negative electrode materials prepared in Examples 1 to 7 and Comparative Examples 1 to 4 were calculated according to the first reversible specific capacity of the button battery, and a certain amount of the same graphite negative electrode was mixed, and each silicon-carbon negative electrode material was mixed to 600±5mAh / g to obtain a mixed negative electrode material. The mixed negative electrode material, the aqueous dispersion of the binder acrylonitrile multipolymer (LA132, solid content 15%) and the conductive agent (Super-P) were mixed in a mass ratio of 92:6:2, and a certain amount of water was added as a solvent for homogenization. The solid content of the slurry was adjusted to 55%, coated on a copper foil, and vacuum dried and rolled to prepare a negative electrode sheet. CR2032 button batteries were assembled in a glove box filled with inert gas, in which the counter electrode was a metal lithium sheet and the electrolyte was 1 mol / L LiPF 6 solution (the solvent is a mixture of EC, DMC and EMC in a volume ratio of 1:1:1), and the separator is a polypropylene microporous membrane.
[0168] Full charge expansion test: Use a micrometer to test the thickness of the negative electrode plate and record it as t1, and the thickness of the copper foil is recorded as t2; perform charge and discharge tests on the button half-cell, 0.1C constant current charge and discharge, the charge and discharge voltage is limited to 0.005-1.5V, and the thickness of the electrode tested in the fully charged state after one cycle is recorded as t3. The first full charge expansion rate = (t3-t1) / (t1-t2)×100%.
[0169] Rate performance test: Under normal temperature conditions, the battery was cycled at 0.1C for 5 weeks, then cycled at 0.2C for 5 weeks, 0.5C for 5 weeks, 1C for 5 weeks, 2C for 5 weeks, and finally 0.1C for 5 weeks, and the 2C discharge capacity retention rate was calculated. The 2C discharge capacity retention rate is the ratio of the lithium-free capacity after 2C current cycling for 5 weeks to the first 0.1C current cycling for 5 weeks.
[0170] Cyclic performance test: Under normal temperature conditions, 1C constant current charge and discharge to 0.01V, then 0.05C constant current discharge to 0.005V, and finally 1C constant current charge to 1.5V to obtain the de-lithiation specific capacity. This cycle is repeated 300 times, and the capacity retention rate after 300 cycles is calculated. The 300-week capacity retention rate is the ratio of the de-lithiation specific capacity in the 300th week to the de-lithiation specific capacity in the first week.
[0171] The silicon-carbon negative electrode materials prepared in Examples 1 to 7 and Comparative Examples 1 to 4 were mixed evenly with graphite in a mass ratio of 5:95 as a composite negative electrode active material, and NCM622 was used as the positive electrode active material. The soft-pack batteries were assembled through the processes of slurry mixing, coating, rolling, slitting, die cutting, lamination, welding of pole ears, top and side sealing, baking, and liquid injection. After the batteries were divided into components, the high-temperature storage performance was tested.
[0172] High temperature storage performance test: Under normal temperature conditions, the soft pack battery is charged to 4.2V at 0.5C, then 4.2V at 0.5C constant voltage, charged to a cut-off current of 0.05C, and then discharged to 3.0V at 0.5C constant current, and the battery capacity C0 is recorded. Then charge to 4.2V at 0.5C, then 4.2V at 0.5C constant voltage, and charge to a cut-off current of 0.05C. After being placed in a 60°C environment for 14 days, the battery is placed in a 25°C environment for 2h, and then discharged to 3.0V at 0.5C constant current, and the battery capacity C1 is recorded. Then charge to 4.2V at 0.5C, then 4.2V at 0.5C constant voltage, and charge to a cut-off current of 0.05C, and then discharge to 3.0V at 0.5C constant current, and the battery capacity C2 is recorded, and the capacity retention rate and capacity recovery rate are calculated. The capacity remaining rate is the ratio of C1 to C0, and the capacity recovery rate is the ratio of C2 to C0.
[0173] Table 2 Performance test results of silicon-carbon negative electrode materials of Examples 1 to 7 and Comparative Examples 1 to 4
[0174]
[0175] Continued from previous table
[0176]
[0177]
[0178] Among them, the carbon nanotube content is obtained by an indirect method. The residual carbon rate of the carbon source under specific temperature and carbonization conditions is determined as a value, so the carbon nanotube content of the carbon assembly can be calculated, and then the carbon nanotube content in the silicon-carbon negative electrode material can be indirectly determined.
[0179] From the results in Table 2, it can be seen that the ultimate compaction density, rate performance and expansion performance of Examples 1 to 7 are all better, because Examples 1 to 7 deposit the nano-silicon particles in the pipes of the carbon nanotubes in the carbon assembly particles. The carbon nanotubes can inhibit the volume change of the nano-silicon particles in the pipes during the charge and discharge process, and the high strength of the carbon nanotubes and the constructed three-dimensional conductive network are conducive to the improvement of the compressive performance and rate performance of the silicon-carbon negative electrode material.
[0180] In Comparative Example 1, nano-silicon is deposited on porous carbon as a matrix, and its porous structure and numerous defects easily lead to low compressive strength and poor rate performance.
[0181] By comparing Example 1 and Comparative Example 2, it can be seen that the average length of the carbon nanotubes used in Comparative Example 2 is smaller than the Dv50 of the carbon assembly, that is, after air flow crushing, there are still more carbon nanotubes embedded in the amorphous carbon of the carbon assembly particles, resulting in more carbon nanotubes being sealed and the pore volume of the carbon assembly particles being smaller, which in turn causes more nano-silicon to be deposited on the surface of the carbon assembly particles rather than in the pipes of the carbon nanotubes, affecting the conductivity of the silicon-carbon negative electrode material. At the same time, its silicon distribution is uneven, resulting in poor rate performance and cycle performance of the silicon-carbon negative electrode material.
[0182] By comparing Example 1 and Comparative Example 3, it can be seen that after airflow pulverization in Comparative Example 3, the pulverization degree B value of the carbon assembly particles is 0.7, which is less than 0.75, that is, the carbon assembly particles are not completely pulverized, and more carbon assembly particles are not pulverized, which ultimately makes more carbon nanotubes sealed. After silicon deposition, most of the nano-silicon particles are distributed on the surface of the carbon assembly particles, which ultimately leads to low conductivity, poor rate performance and cycle performance of the silicon-carbon negative electrode material, and the agglomeration of nano-silicon particles on the surface also affects the full-charge expansion rate and the ultimate compaction density.
[0183] By comparing Example 1 and Comparative Example 4, it can be seen that the inner diameter of the carbon nanotubes used in Comparative Example 4 is larger, and the pore volume of the carbon assembly particles is not much different, but the larger inner diameter causes more nano-silicon particles to accumulate in the same carbon nanotube during the silicon deposition process. Compared with Example 1, the dispersion uniformity of the nano-silicon particles is deteriorated, which can easily lead to poor electrical contact during the cycle process, thereby affecting the rate performance and cycle performance of the silicon-carbon negative electrode material.
[0184] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. Silicon-carbon negative electrode material, characterized in that: The invention comprises carbon assembly particles, nano silicon particles and a carbon coating layer. The carbon assembly particles are a composite of carbon nanotubes and amorphous carbon. The nano silicon particles are contained in the pipes of the carbon nanotubes, and the carbon coating layer covers the carbon assembly particles.
2. The silicon-carbon negative electrode material according to claim 1, characterized in that: Satisfies the following relationship, Wherein, L is the full charge expansion rate of the silicon-carbon negative electrode material, %; M is the percentage of the carbon nanotubes in the total mass of the silicon-carbon negative electrode material, %; N is the percentage of the nano-silicon particles in the total mass of the silicon-carbon negative electrode material, %; ρ is the ultimate compaction density of the silicon-carbon negative electrode material, g / cm 3 ; B is the degree of crushing of the carbon assembly particles.
3. The silicon-carbon negative electrode material according to claim 2, characterized in that: 0.75≤B≤1.00。 4. The silicon-carbon negative electrode material according to claim 1, characterized in that: Contains at least one of the following features (1) to (26): (1) The first reversible capacity of the silicon-carbon negative electrode material is ≥ 900.0 mAh / g; (2) The first coulombic efficiency of the silicon-carbon negative electrode material is ≥89.0%; (3) The 2C discharge capacity retention rate of the silicon-carbon negative electrode material is ≥ 90.0%; (4) The 300-cycle capacity retention rate of the silicon-carbon negative electrode material is ≥ 88.0%; (5) The first full charge expansion rate of the silicon-carbon negative electrode material is ≤30.0%; (6) The tap density of the silicon-carbon negative electrode material is 0.8 to 1.5 g / cm 3 ; (7) The true density of the silicon-carbon negative electrode material is 1.5 to 2.0 g / cm 3 ; (8) The ultimate compaction density of the silicon-carbon negative electrode material is 1.5 to 2.0 g / cm 3 ; (9) The specific surface area of the silicon-carbon negative electrode material is 1 to 10 m 2 / g; (10) The Dv50 of the silicon-carbon negative electrode material is 3 to 15 μm; (11) The electrical conductivity of the silicon-carbon negative electrode material is 2.0 to 5.0 S / cm. (12) At least a portion of the carbon nanotubes in the carbon assembly particles are accessible to nitrogen; (13) The pore volume of the carbon assembly particles is 0.15 to 0.45 cm 3 / g; (14) The average pore size of the carbon assembly particles is 1.5 to 4.5 nm; (15) The porosity of the carbon assembly particles is 20 to 70%; (16) The specific surface area of the carbon assembly particles is 400 to 1200 m 2 / g; (17) The Dv50 of the carbon assembly particles is 3 to 15 μm; (18) The Dv50 of the carbon assembly particles is less than the average length of the carbon nanotubes; (19) The amorphous carbon includes at least one of soft carbon and hard carbon; (20) The carbon nanotubes include at least one of single-walled carbon nanotubes and multi-walled carbon nanotubes; (21) The average length of the carbon nanotubes is 5 to 20 μm, and the inner diameter of the tubes is 0.5 to 5.0 nm; (22) The carbon nanotubes account for 20 to 60% of the total mass of the silicon-carbon negative electrode material; (23) The nano silicon particles account for 10 to 40% of the total mass of the silicon-carbon negative electrode material; (24) The nano silicon particles are amorphous silicon, and the grain size of the amorphous silicon is ≤3 nm; (25) The thickness of the carbon coating layer is 10 to 300 nm; (26) The carbon coating layer accounts for 0.5 to 10.0% of the total mass of the silicon-carbon negative electrode material.
5. A method for preparing a silicon-carbon negative electrode material, characterized in that: Includes steps: (I) mixing carbon nanotubes, a first carbon source and an organic solvent to obtain a slurry, spray drying the slurry and then carbonizing the slurry to obtain a carbon precursor, wherein the inner diameter of the carbon nanotubes is d, the average length of the carbon nanotubes is L, and 0.5 nm≤d≤5.0 nm; (II) crushing the carbon precursor to obtain carbon assembly particles, wherein the degree of crushing of the carbon assembly particles is B, 0.75≤B≤1.00, and L is greater than or equal to Dv50 of the carbon assembly particles; (III) subjecting the carbon assembly particles to vapor phase silicon deposition and then carbon coating with a second carbon source.
6. The method for preparing the silicon-carbon negative electrode material according to claim 5, characterized in that: Contains at least one of the following features (i) to (xiv): (i) the first carbon source comprises at least one of petroleum coke, asphalt, phenolic resin, urea-formaldehyde resin, polyamide resin, epoxy resin, polyimide, polyvinyl pyrrolidone, polyvinyl alcohol, polyacrylonitrile, polydopamine, sucrose, glucose, starch, lignin, and citric acid; (ii) the organic solvent comprises at least one of methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, propylene glycol, benzene, toluene, xylene, hexane, n-hexane and cyclohexane; (iii) the mass ratio of the carbon nanotubes, the first carbon source and the organic solvent is 1:0.5-5:1-20; (iv) stirring during the mixing, the stirring speed is 100 to 1000 rpm, and the stirring time is 1 to 10 hours; (V) The feed inlet temperature of the spray drying is 120-250°C, and the discharge outlet temperature of the spray drying is 70-110°C; (vi) the carbonization temperature is 600 to 1000° C. and the carbonization time is 1 to 10 hours; (VII) the carbonization is carried out in a protective gas, wherein the protective gas is at least one of nitrogen, helium, neon, argon, krypton and xenon; (VIII) The Dv50 of the carbon assembly particles is 5 to 25 μm; (IX) The pulverization is carried out by using a jet mill; (10) The temperature of the carbon coating is 500 to 900° C., and the time of the carbon coating is 1 to 8 hours; (XI) the second carbon source is a gaseous carbon source, and the gaseous carbon source includes at least one of methane, ethane, propane, butane, isobutane, ethylene, propylene, butene and acetylene; (XII) The second carbon source is a gaseous carbon source, and the volume concentration of the gaseous carbon source is 5 to 50%; (XIII) The carbon coating is carried out in a protective gas, wherein the protective gas is at least one of nitrogen, helium, neon, argon, krypton and xenon; (XIV) After the carbon coating, the process also includes sequentially breaking up, screening and demagnetizing treatment.
7. The method for preparing the silicon-carbon negative electrode material according to claim 5, characterized in that: The vapor phase silicon deposition comprises the steps of: subjecting the carbon assembly particles and silicon source gas to chemical vapor deposition in a high temperature environment.
8. The method for preparing the silicon-carbon negative electrode material according to claim 7, characterized in that: Contains at least one of the following features (i) to (i): (i) The temperature of the high temperature environment is 400-700° C.; (ii) the chemical vapor deposition time is 1 to 8 hours; (iii) the silicon source gas comprises at least one of monosilane, disilane, trisilane, monochlorotrihydrogensilane, dichlorodihydrogensilane and trichlorosilane; (iv) the volume concentration of the silicon source gas is 5 to 40%; (v) the nano-silicon particles formed by the pyrolysis of the silicon source gas are at least partially distributed in the channels of the carbon nanotubes in the carbon assembly; (vi) The vapor phase silicon deposition is carried out in a protective gas, and the protective gas is at least one of nitrogen, helium, neon, argon, krypton and xenon.
9. Use of the silicon-carbon negative electrode material prepared by the silicon-carbon negative electrode material according to any one of claims 1 to 4 or the method for preparing the silicon-carbon negative electrode material according to any one of claims 5 to 8 in a negative electrode.
10. A secondary battery comprising a positive electrode active material, a negative electrode active material and an electrolyte, characterized in that: The negative electrode active material includes the silicon-carbon negative electrode material according to any one of claims 1 to 4 or the silicon-carbon negative electrode material prepared by the method for preparing the silicon-carbon negative electrode material according to any one of claims 5 to 8.